A study on the effect of microwave radiation exposure time on the properties of devulcanized EPDM waste / Norhidayah Ahmad Jalini - Ahmad Jalini, Norhidayah (2020)
The highly demanding of Ethylene-Propylene-Diene Monomer (EPDM) in industries due to its outstanding characteristic such as resistance to oxygen and ozone make the EPDM as one of the fastest-growing general purpose rubber nowadays. However, the demand may cause the increasing of the abundant waste rubber as it is difficult to dispose due to its crosslinks network which form during vulcanization. Thus, it lead to the rising of the land cost, environmental concerns and other problems. In order to manage this abundant waste rubber, a devulcanization process can be done. There are a lot of devulcanized method can be chose to handle the waste rubber. But devulcanized by microwave radiation is chosen in this research. Different exposure times (3, 5, 7 and 9 minutes) to the radiation were used. The cure characteristics, tensile properties, hardness, crosslink density, abrasion resistance and FTIR analysis of NR blends with devulcanized EPDM were measured. Results show that 5 minutes exposure time increased the tensile strength, tensile strain, hardness value and crosslink density. The formation of a new bond which is the S-O bond at 962.3 cm-1 893 cm-1 and the disappeared of the C-S bond at 1272 cm-1 demonstrate by the FTIR spectra might be the factor of the best results obtained at 5 minutes of exposure time.